Development of a Patient Decision Aid for Syncope in the Emergency Department: the SynDA Tool. (20th February 2018) - Probst, Marc A.; Hess, Erik P.; Breslin, Maggie; Frosch, Dominick L.; Sun, Benjamin C.; Langan, Marie‐Noelle; Richardson, Lynne D.
Abstract: Objectives: The objective was to develop a patient decision aid (DA) to promote shared decision making (SDM) for stable, alert patients who present to the emergency department (ED) with syncope. Methods: Using input from patients, clinicians, and experts in the field of syncope, health care design, and SDM, we created a prototype of a paper‐based DA to engage patients in the disposition decision (admission vs. discharge) after an unremarkable ED evaluation for syncope. In phase 1, we conducted one‐on‐one semistructured exploratory interviews with 10 emergency physicians and 10 ED syncope patients. In phase 2, we conducted one‐on‐one directed interviews with 15 emergency care clinicians, five cardiologists, and 12 ED syncope patients to get detailed feedback on DA content and design. We iteratively modified the aid using feedback from each interviewee until clarity and usability had been optimized. Results: The 11 × 17‐inch, paper‐based DA, titled SynDA, includes four sections: 1) explanation of syncope, 2) explanation of future risks, 3) personalized 30‐day risk estimate, and 4) disposition options. The personalized risk estimate is calculated using a recently published syncope risk‐stratification tool. This risk estimate is stated in natural frequency and graphically displayed using a 100‐person color‐coded pictogram. Patient‐oriented questions are included to stimulate dialogue between patient and clinician. At the end of the development process, patient and physician participants expressed satisfaction with the clarity and usability of the DA. Conclusions: We iteratively developed an evidence‐based DA to facilitate SDM for alert syncope patients after an unremarkable ED evaluation. Further testing is required to determine its effects on patient care. This DA has the potential to improve care for syncope patients and promote patient‐centered care in emergency medicine.